As bonitezas de um programa de extensão na formação de acadêmicos(as) de Educação Física a partir de suas vivências - Porto, Ádria Monique Santarém (Brasil, 2024)
The University, this space of sharing, provides opportunities for various experiences of the goodness of education. It is promising in the commitment to actions and effective reflection of professional training for teaching. It is from this assumption that the extension and learning must be in line with the guidelines and projects of the higher education institution. Thus, this research aimed to analyze experiences of Physical Education academic(s) in a university extension program in Parintins before the process of professional training. The research is presented as descriptive with qualitative approach. The participants were 8 Physical Education academics (as) who act or acted in a program of dance extension, circus activities and gymnastics in Parintins. The (s) academic(s) who participated in the research signed the Informed Consent Form (FCE). For data collection, a semi-structured interview was conducted in face-to-face format. The data were analyzed from the technique of Elaboration and Analysis of Units of Meaning according to Moreira, Simões and Porto (2008) this technique follows three important moments, which are: naive report, identification of attitudes and interpretation. The results reveal that the participation of academics in the extension program Prodagin, allowed them a new look on the practices of dance, circus and gymnastics activities, contemplating the various gaps that were present in these areas before entering the program, also contributing to their training as future professionals in the area, as well as allowing them to understand the importance of the indissociability of education and extension program.